Analisa Tingkat Kepuasan Pelayanan pada Aplikasi PLN Mobile dengan Metode Service Quality - Nu’man Nashif Annawwaf; Nur Nawaningtyas Pusparini (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This study aims to analyze user satisfaction with the PLN Mobile application using the Service Quality (SERVQUAL) method. PLN Mobile is a digital innovation from PLN, offering services such as electricity payment, token purchase, and e-commerce for electrical equipment. The SERVQUAL method assesses the gap between customers' expectations and perceptions across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data collection involved questionnaires focusing on users' perceptions and expectations, complemented by direct observations of user interactions with the application. The findings reveal negative gaps across all Service Quality dimensions, indicating that customer perceptions fell short of their expectations. The largest gap was identified in the assurance dimension (-23.2), followed by responsiveness (-16.88). The tangibles dimension also showed significant shortcomings (-8.48), mainly concerning the application's interface and functionality. While the application performed relatively well in terms of reliability and responsiveness, substantial improvements are needed across all dimensions to enhance user satisfaction. These results offer strategic insights for improving PLN Mobile to become more responsive, reliable, and aligned with user needs in the future.